2019
DOI: 10.9734/ajacr/2019/v4i1-230105
|View full text |Cite
|
Sign up to set email alerts
|

Towards Greener Preservation of Edible Oils: A Mini-review

Abstract: Edible oils like sunflower oil, rapeseed oil, soybean oil, cotton seed oil and olive oil are necessary components in human diet and are extensively utilized in the food trade. Safe storage of edible oils has perpetually been a haul within the food industry since the oils can easily endure oxidative deterioration. Studies specializing on polyphenols as a supply of natural antioxidants of plant origin to delay oxidative deterioration of food products have increased worldwide. Both natural and synthetic antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, they are inevitable components of daily cooking, and their consumption is intensively growing all over the world (Patel & Dewettinck, 2016). They can be either natural (i.e., extracted from natural sources such as seeds, vegetables, or animals) or synthetic (synthesized fats; Tapera, 2019). Natural oils (esp.…”
Section: Secondary Data Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are inevitable components of daily cooking, and their consumption is intensively growing all over the world (Patel & Dewettinck, 2016). They can be either natural (i.e., extracted from natural sources such as seeds, vegetables, or animals) or synthetic (synthesized fats; Tapera, 2019). Natural oils (esp.…”
Section: Secondary Data Reviewmentioning
confidence: 99%
“…Water scarcity is predicted to get more intensive in the forthcoming years (Piesse, 2020). Statistical data demonstrated that annual water consumption in three main different sectors of agriculture, industries, and urban is about 4 trillion cubic meters with an intensive increase (Tapera, 2019). However, accessible freshwater for human activities is only about 0.01 trillion cubic meters (Awange, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is continuously an increasing research interest in exploration of antioxidants from natural sources such as plants (Bera et al, 2006;Blasi and Cossignani, 2020;Metzner and Poiana, 2018). The enhanced antioxidant activity of plant derived materials has been well proven as they are rich in fla-vonoids and polyphenols (Shadyro et al, 2017;Tapera, 2019;Waheed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Statistics indicate an increasing demand for soybean, palm, and rapeseed oil. In 2019, the consumption of palm, soybean, and rapeseed reached 71.48, 55.46, and 45.27 million tons, respectively [50,51].…”
Section: Fish and Seafood Industriesmentioning
confidence: 99%